The Spirit of Logotherapy - Costello, Stephen J. (2016)
The aim of this paper is to adduce the meaning of Viktor Frankl's logotherapy and existential analysisthe spirit of logotherapyin the two-fold sense of its core teachings, as well as its emphasis on the spiritual dimension of the human person. Firstly, I situate Frankl's tri-dimensional ontologyhis philosophical anthropologywithin a Platonic perspective, asserting that it was Plato who first gave us a picture and model of mental health which he based on the harmony of the disparate parts of the personalitythe aim to become One instead of Many, which finds a modern parallel in Viktor Frankl's logotherapy, which likewise stresses the importance of inner wholeness (an anthropological oneness) despite our ontological differences. Classical Greek philosophers all pointed to the Logos as source of orderto the horizon of meaning-potentials, so I visit the various understandings of this term from the pre-Socratics to Frankl, albeit briefly, to avoid semantic confusion in what is to follow. I then discuss in some detail the exact meaning that logos/spirit has in Frankl's philosophical conceptualisations. Disorders of logos may be seen in various psychopathologies and pnemopathologies which I go on to consider, highlighting the differences between various terms that are commonly left unclarified. Next, I adumbrate the differences between psychotherapy and logotherapy, which ultimately revolves around the difference between instincts and spirit before demarcating the boundaries between religion (as salvation) and logotherapy (as sanity). The question I pose next is: what exactly constitutes the spiritual in logotherapy, as in life? An example is given to concretise the conceptual considerations previously elucidated before drawing on another distinction, that between ultimate meaning and the meaning of the moment. The paper concludes with a brief excursus into the work of Ken Wilber by way of enabling us to appreciate and better understand the monumental significance of Frankl's contribution to the field of transpersonal studies in relation to his refusal to collapse, confuse or conflate the higher dimensions of the person into lower ones.
Keywords: Plato; Viktor Frankl; Voegelin; Existential Analysis; Logotherapy; Meaning; Spirit; tri-dimensional ontology